PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL HARPER MANGKUBUMI YOGYAKARTA - Pansla, Rafiand Amirul (journal of residu, 2019)
This study aims to determine the effect of work discipline on the performance of employees at the harper mangkubumi hotel in Yogyakarta. This research is a quantitative descriptive study with a causal associative approach. The number of samples in this study were 71 samples. The sampling method is by saturated sampling technique. Data was collected using a questionnaire using a Likert scale. The data analysis technique used in this study is descriptive analysis using simple linear regression analysis. The results of this study indicate that: (1) work discipline is in the good category 53.5%, (2) employee performance is in the good category 52.1%, (3) there is a value of work discipline increasing by 0.346 units with the assumption of permanent work discipline. While the magnitude of the influence of work discipline on the performance of employees in the harper mangkubumi hotel in Yogyakarta is 18% and 82% is influenced by other factors.